Analisis Minat Belajar Siswa Dalam Belajar Online di Era Covid-19 - Amelia Amelia; Agus Suryana; Herlina Herlina (EduInovasi: Journal of Basic Educational Studies, 2022)
This article aims to determine the analysis of students' interest in learning online in the Covid-19 era. The method used is a case study with interview and observation techniques. This research was conducted in the Tajurhalang District, Sukmajaya Villag3 Depok City. The results of the analysis of students' interest in learning online during the Covid-19 era show that the interest in learning that occurs in students is due to factors from themselves, parents, and the surrounding environment. Keywords: interest in learning, students, online learning, the covid-19 pandemic